2022
DOI: 10.1108/jhti-11-2021-0312
|View full text |Cite
|
Sign up to set email alerts
|

Understanding tourists' policing attitudes and travel intentions towards a destination during an ongoing social movement

Abstract: PurposePolicing activities aim to provide a safe environment for tourists. With the recent major protests that have erupted around the world, and the novel use of excessive police force against protestors, people may wonder if the policing deployment is for destination safety or to deter tourists from visiting. This paper aims to investigate anti-police and pro-police attitudes and tourists' behavioural responses towards a popular destination experiencing an ongoing social movement.Design/methodology/approachD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…The research studied the influence social media marketing had on characteristics like destination image and visited intentions (Lai et al , 2022). The findings partially corroborated the preceding study's conclusions (Chang et al , 2020; Sun et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The research studied the influence social media marketing had on characteristics like destination image and visited intentions (Lai et al , 2022). The findings partially corroborated the preceding study's conclusions (Chang et al , 2020; Sun et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…DI research so far has concluded the inability of promotional materials to alter the existing organic images of various destinations (Dogra and Karri, 2021;Hankinson, 2004). DS further contributes to this notion as it is rooted in the subject's confirmation bias (Lai et al, 2022) and as asserted by Nickerson (1998, p. 209), it "must be recognized as a major force that works against easy and frequent opinion change." However, by considering DS and addressing the prime cause of such a perception, DI can be altered for good and more importantly in an effective manner.…”
Section: Practical Implicationsmentioning
confidence: 96%
“…As such, marketing of a destination begins from a pre-existing notion, whether positive or negative, and not necessarily from a neutral base (Hankinson, 2004). Given the way organic images are formed, they cannot be knocked down but only altered through actual visits (Andsager and Drzewiecka, 2002;Lai et al, 2022;Laxson, 1991).…”
Section: Components and Formation Of Destination Imagementioning
confidence: 99%
“…It will enhance the danger of hazards other than COVID-19, causing individuals to be cautious about selecting this location. Customers dislike it when the police make an unwelcome appearance in a popular tourist destination and respond aggressively to how visitors behave there (Lai et al, 2022). Using nonthreatening uniforms or staying safe while being protected by local authorities, if implemented simultaneously, will aid in regional tourism growth (Sousa and Alves, 2019).…”
Section: Knowledge Of Covid-19mentioning
confidence: 99%